Seed Quality Assessment through Incubation, Drying and Separation (IDS) in Silver Fir (Abies pindrow Spach) - Singh, Virendra; Singh, Ajay Kumar (Indian Forester, 2015)
The seeds were incubated in different specific gravity solutions for 24 hours at room temperature (maximum 10.61Â°C and minimum 7.35Â°C). Thereafter, the sunken and floater seeds were taken out separately from the solutions and were spread on filter paper thinly for drying for o hour (no drying), 2 hour, and 4 hour and tested for seed germination. The results of the study revealed that the sunken seeds separated by IDS method resulted in higher germination as compared to floater seeds. The sunken seeds which were dried for 0 hour (no drying) resulted in 96.61% germination and the subsequent drying led to decrease in germination. The germination of seeds in control (without soaking and drying) was only 27.00 per cent. Therefore, the sunken seeds in 1.0 specific gravity solution without drying should be used to get the higher germination of seeds.